2009
DOI: 10.1017/s001675680999001x
|View full text |Cite
|
Sign up to set email alerts
|

Fissure fills along faults: Variscan examples from Gower, South Wales

Abstract: -The extent to which persistent, rather than transient, fissures (wide planar voids) can exist along upper crustal faults is important in assessing fault permeability to mineral and hydrocarbonbearing fluids. Variscan (late Carboniferous) faults cutting Dinantian (Lower Carboniferous) limestones on the Gower peninsula, South Wales, host clear evidence for fissures up to several metres wide. Evidence includes dendritic hematite growth and elongate calcite growth into open voids, spar ball and cockade breccia fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…The age of the Gower fault fissures is unproven. Wright et al (2009) suggested a late Variscan age, but we favour the Triassic age suggested by Strahan (1907) on the basis of supposedly Triassic red sandstones unconformably overlying the Pembroke Group at Port Eynon. A later age cannot be ruled out.…”
Section: Regional Pattern Of Dilational Faultingsupporting
confidence: 44%
See 3 more Smart Citations
“…The age of the Gower fault fissures is unproven. Wright et al (2009) suggested a late Variscan age, but we favour the Triassic age suggested by Strahan (1907) on the basis of supposedly Triassic red sandstones unconformably overlying the Pembroke Group at Port Eynon. A later age cannot be ruled out.…”
Section: Regional Pattern Of Dilational Faultingsupporting
confidence: 44%
“…3c). Wright et al (2009) studied strike-slip cross faults in the Pembroke Group of the Gower Peninsula, there contain void-filling veins and breccias produced during active faulting rather than by solution. One of the westernmost faults contains megabreccia identical to the Pembrokeshire examples.…”
Section: Previous Work and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…A pure tectonically related mechanical diminution or abrasion scenario (Jébrak, 1997;Keulen et al, 2007;Mort and Woodcock, 2008;Wright et al, 2009) Another scenario comprises the dissolution of local patches of sulphates which requires a brine density flow (Anderson and Kirkland, 1980) triggered by pressurized meteoric water exploring a present fracture system. The potential presence of some sulphate minerals is supported by the presence of celestite laths within and next to the SSB fabric.…”
Section: Accepted Manuscriptmentioning
confidence: 99%